Activation of the Adipose Tissue NLRP3 Inflammasome Pathway in Cancer Cachexia - Jesus, Joyce de Cassia Rosa de; Murari, Ariene Soares de Pinho; Radloff, Katrin; Moraes, Ruan Carlos Macêdo de; Figuerêdo, Raquel Galvão; Pessoa, Ana Flavia Marçal; Rosa-Neto, José César; Matos-Neto, Emídio Marques; Alcântara, Paulo S. M.; Tokeshi, Flavio; Maximiano, Linda Ferreira; Bin, Fang Chia; et al. (Frontiers in Immunology, 2021)
Background Cachexia is a paraneoplastic syndrome that accompanies and compromises cancer treatment, especially in advanced stages, affecting the metabolism and function of several organs. The adipose tissue is the first to respond to the presence of the tumor, contributing to the secretion of factors which drive the systemic inflammation, a hallmark of the syndrome. While inflammation is a defensive innate response, the control mechanisms have been reported to be disrupted in cachexia. On the other hand, little is known about the role of NLRP3 inflammasome in this scenario, a multiprotein complex involved in caspase-1 activation and the processing of the cytokines IL-1β and IL-18. Aim based on the evidence from our previous study with a rodent model of cachexia, we examined the activation of the NLRP3 inflammasome pathway in two adipose tissue depots obtained from patients with colorectal cancer and compared with that another inflammatory pathway, NF-κB. Results For CC we found opposite modulation in ScAT and PtAT for the gene expression of TLR4, Caspase-1 (cachectic group) and for NF-κB p50, NF-κB p65, IL-1β. CD36, expression was decreased in both depots while that of NLRP3 and IL-18 was higher in both tissues, as compared with controls and weight stable patients (WSC). Caspase-1 basal protein levels in the ScAT culture supernatant were higher in WSC and (weight stable patients) CC, when compared to controls. Basal ScAT explant culture medium IL-1β and IL-18 protein content in ScAT supernatant was decreased in the WSC and CC as compared to CTL explants. Conclusions The results demonstrate heterogeneous responses in the activation of genes of the NLRP3 inflammasome pathway in the adipose tissue of patients with cancer cachexia, rendering this pathway a potential target for therapy aiming at decreasing chronic inflammation in cancer.